Microfluidics‐Assisted TIRF Imaging to Study Single Actin Filament Dynamics. Issue 1 (13th February 2018) - Shekhar, Shashank
Abstract: Dynamic assembly of actin filaments is essential for many cellular processes. The rates of assembly and disassembly of actin filaments are intricately controlled by regulatory proteins that interact with the ends and the sides of filaments and with actin monomers. TIRF‐based single‐filament imaging techniques have proven instrumental in uncovering mechanisms of actin regulation. In this unit, novel single‐filament approaches using microfluidics‐assisted TIRF imaging are described. These methods can be used to grow anchored actin filaments aligned in a flow, thus making the analysis much easier as compared to open flow cell approaches. The microfluidic nature of the system also enables rapid change of biochemical conditions and allows simultaneous imaging of a large number of actin filaments. Support protocols for preparing microfluidic chambers and purifying spectrin‐actin seeds used for nucleating anchored filaments are also described. © 2017 by John Wiley & Sons, Inc.